Nanofibrous Membrane for Biomedical Application - Ehrmann, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Electrospinning can be used to prepare nanofibrous membranes from diverse polymers. The large surface-to-volume ratio makes them suitable for diverse fields of applications, from filters to catalysts to tissue engineering.Here, we search for the latest developments dealing with nanofiber mats for biomedicine. From wound healing to slow release, and from tissue engineering to stem cell differentiation, nanofibrous membranes can be found in a broad range of biomedical applications. For these utilizations, their chemical as well as physical properties are important, such as hydrophobicity, fiber morphology, membrane porosity, mechanical strength, etc. This Special Issue focuses on nanofibrous membranes for biomedical applications, measuring and optimizing the correlated membrane properties. It covers the full range from basic research on new materials and producing novel electrospun structure to drug release to cell growth on nanofiber mats.